Past century changes in Araucaria angustifolia (Bertol.) Kuntze water use efficiency and growth in forest and grassland ecosystems of southern Brazil: implications for forest expansion - SILVA, LUCAS C.R; ANAND, MADHUR; OLIVEIRA, JULIANO M; PILLAR, VALÉRIO D (Global change biology, 2009)
Araucaria angustifolia (Bertol.) Kuntze is an indigenous conifer tree restricted to the southern region of South America that plays a key role in the dynamics of regional ecosystems where forest expansion over grasslands has been observed. Here, we evaluate the changes in intrinsic water use efficiency (iWUE) and basal area increment (BAI) of this species in response to atmospheric CO₂, temperature and precipitation over the last century. Our investigation is based on tree-rings taken from trees located in forest and grassland sites in southern Brazil. Differences in carbon isotopic composition (δ¹³C), ¹³CO₂ discrimination (Δ¹³C) and intracellular carbon concentration (Ci) are also reported. Our results indicate an age effect on Δ¹³C in forest trees during the first decades of growth. This age effect is not linked to an initial BAI suppression, suggesting the previous existence of nonforested vegetation in the forest sites. After maturity all trees show similar temporal trends in carbon isotope-derived variables and increasing iWUE, however, absolute values are significantly different between forest and grassland sites. The iWUE is higher in forest trees, indicating greater water competition or nutritional availability, relative to grassland, or both. BAI is also higher in forest trees, but it is not linked with iWUE or atmospheric CO₂. Nevertheless, in both forest and grassland sites A. angustifolia has had growth limitations corresponding to low precipitation and high temperatures observed in the 1940s.